A low-roughness composite titanium nitride coating and preparation method thereof

By preparing a composite titanium nitride coating with low roughness on the artificial joint friction surface, the problem of difficulty in reducing the coating roughness in the prior art is solved, coating performance that meets industry standards is achieved, and service life is extended.

CN118497667BActive Publication Date: 2025-02-07CHONGQING BIOINTELLIGENT MFG RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410543671.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-12
Publication Date
2025-02-07
Estimated Expiration
2043-12-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the roughness of the titanium nitride coating on the friction surface of artificial joints, and cannot meet the requirements of the roughness of the friction surface of joint prosthesis in industry standards.

Method used

A low-roughness composite titanium nitride coating is used to prepare a low-roughness composite titanium nitride coating, including polishing the titanium alloy matrix material, depositing Ti and TiN layers in the anode ion beam using a vacuum coating equipment, and adjusting the sample suspension height and rotation angle , combined with the physical barrier of the mask plate, a double-layer structural coating with a surface roughness of less than 100 nm was prepared.

Benefits of technology

It realizes a low-rough coating on the artificial joint friction surface, meets the industry standards for the roughness of the friction surface of joint prosthesis, and improves the wear resistance and service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118497667B_ABST
    Figure CN118497667B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of artificial joint technology, and specifically relates to a low-roughness composite titanium nitride coating and a preparation method thereof. The method of the present invention first adjusts the suspension position of a titanium alloy base material, and then adjusts the base material suspension height within a range of 0-90° upwards based on the horizontal direction of a cathode arc target; further, the base material is rotated at a fixed angle relative to the front of the cathode arc target for uniform deposition, and finally a low-roughness composite titanium nitride coating is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Divisional application

[0002] This application is a divisional application based on the Chinese invention patent application with application number CN202311707981.9, application date December 12, 2023, and invention name "Low-roughness titanium nitride coating and preparation method for artificial joint friction surface". Technical Field

[0003] The invention belongs to the technical field of artificial joints, and particularly relates to a low-roughness composite titanium nitride coating and a preparation method thereof. Background Art

[0004] Arc Ion Plating is a surface coating technology. The basic principle is to form an arc plasma between the anode and cathode targets through arc discharge generated in a vacuum environment. There are high-density electron flows, metal ion flows and metal vapor flows in the arc plasma. The energy of the ions is used to evaporate or sputter the source material into an ion state, and then the bias electric field is used to deposit the material on the surface of the substrate to form a coating.

[0005] The advantage of arc ion plating process is that it has a high deposition rate and a high ionization rate, but the solitary light discharge process causes the temperature of the cathode target surface to rise very quickly, causing the target to melt and spray in a short time, resulting in a large number of metal droplets in the deposited film, which is usually called "large particle defects". The size of large particles can reach up to 10μm, which will have a significant impact on the performance of the coating, such as increasing the roughness of the coating, reducing the density and corrosion resistance of the coating. Therefore, reducing the content of large particles and reducing the roughness of the coating through technical optimization is an effective technical approach to extend the service life of the coating and avoid premature failure of the coating. The existing technical view is that since the three cores of arc ion plating technology are power supply, target material and its constraining magnetic field, the droplets and microscopic defects of the coating can be reduced by reasonably regulating the process parameters of current, air pressure and magnetic field.

[0006] The patent with application number CN201710615549.5 and invention name "Process for preparing nitrogen-based hard coating by adjustable magnetic field arc ion plating" discloses a method to adjust the power supply parameters of the electromagnetic field coil to change the intensity and direction of the electromagnetic field, so that the arc spot can make a stable scaling motion on the target surface with the center of the target material as the center of the circle, and evenly etch the target material, thereby making the single-layer nitrogen-based hard coating have a low friction coefficient, a smooth coating surface and a small number of "large particles". However, the patent does not substantially give the extent of the reduction in roughness, and only uses the change in friction coefficient to represent the change in surface quality. If it is used in fields with clear requirements for surface roughness, it is impossible to expect that its technical effect can meet application scenarios with high surface roughness requirements based on this technical solution alone.

[0007] In the field of metal artificial joint technology, there are clear requirements for the roughness of the coating surface. This is because the friction surface of the artificial joint will face millions of times of friction and wear during actual use in the human body, so the country has promulgated a number of standards to put forward clear requirements for the quality of its friction interface. The group standard "Additive Manufacturing Metal Shoulder Joint Prosthesis" (T / CAMDI 092-2022) and the People's Republic of China Medical Industry Standard YY 0118-2016 both clearly require that the roughness of the friction surface of the joint prosthesis Ra <100nm. This places high demands on the low-cost and controllable industrial preparation of high-quality titanium nitride coating materials used on the surface of artificial joints. Summary of the invention

[0008] In view of this, in order to solve the problem of preparing a low-roughness coating material applied to the friction surface of an artificial joint, the present invention proposes the following technical solution.

[0009] A method for preparing a low-roughness composite titanium nitride coating, the preparation method comprising the following steps:

[0010] S01: using titanium alloy as a base material, and performing a polishing process on the base material;

[0011] S02: placing the polished substrate material on a sample rack of a vacuum coating device and fixing it thereon, and placing the sample rack in a coating chamber of the vacuum coating device for vacuuming;

[0012] S03: rotating the sample holder to the front of the anode layer ion beam, introducing gas to ionize the sample using the anode layer linear ion beam, and etching the surface of the substrate material using the ionized energetic ions to remove the oxide film;

[0013] S04: depositing a first Ti layer on the surface of the base material, and then depositing a second TiN layer; the specific operation is to first adjust the hanging position of the base material, and adjust the hanging height of the base material upward within a range of 0-90° based on the horizontal direction of the cathode arc target; then close the sample holder revolution setting of the vacuum coating equipment, adjust the sample holder to a specific angle relative to the front of the cathode arc target, and keep the sample holder rotating, so that the base material rotates at a fixed angle relative to the front of the cathode arc target; the specific angle relative to the front of the cathode arc target includes 0°, 45° or 60°;

[0014] S05: further arranging a mask plate in front of the base material, wherein the aperture range of the mask plate is 100-300 μm; and finally preparing the low-roughness composite titanium nitride coating on the titanium alloy.

[0015] Furthermore, in step S03, the gas introduced into the vacuum coating equipment is argon gas, and the gas flow rate is 60-120 sccm.

[0016] Furthermore, the base material suspension height is within the range of 60-90° upwards based on the horizontal direction of the cathode arc target.

[0017] Furthermore, the sample holder is fixed at a position of 45° or 60° relative to the front of the cathode arc target; and the sample holder rotates at 10-20 rpm.

[0018] Furthermore, in step S04, argon gas is first introduced to deposit a first Ti layer for a duration of 10-20 minutes, and then nitrogen gas is introduced to deposit a second TiN layer for a duration of 2-4 hours.

[0019] The low-roughness composite titanium nitride coating-titanium alloy material prepared by the above preparation method has a composite titanium nitride coating in the low-roughness composite titanium nitride coating-titanium alloy material as a double-layer structure; the surface roughness of the composite titanium nitride coating is less than 100nm.

[0020] Furthermore, the double-layer structure is a Ti-TiN double-layer structure, wherein the Ti layer is a transition layer between the titanium alloy substrate and the TiN layer.

[0021] Furthermore, the thickness of the Ti layer is 0.1-0.5 μm; the thickness of the TiN layer is 3.0-3.5 μm, and the overall thickness of the coating is 3.5-4.0 μm.

[0022] The use of the low-roughness composite titanium nitride coating-titanium alloy material in the preparation of titanium alloy artificial joints; or, the use of the preparation method of the low-roughness composite titanium nitride coating in the preparation of titanium alloy artificial joints.

[0023] Titanium alloy material itself is very soft, and when used in artificial joint preparation, it needs to be protected to reduce friction and wear. The Ti / TiN coating prepared on the titanium alloy substrate of the present invention can protect the titanium alloy at the friction surface of the all-titanium artificial joint and improve the surface strength of the titanium alloy.

[0024] Beneficial technical effects

[0025] 1) The present invention provides a low-roughness composite titanium nitride coating, the surface roughness of which can be as low as 0.09 μm, meeting the requirements of industry standards and national standards for the roughness of the friction surface of joint prostheses Ra < 100 nm, and thus can be used to prepare titanium alloy artificial joints. The composite titanium nitride coating prepared by the present invention has a lower and more stable friction coefficient after friction test, proving that it can have a longer service life in the application of artificial joints and can be used for a long time in a body fluid environment.

[0026] 2) In the low-roughness composite titanium nitride coating prepared by the present invention, the soft Ti layer is used as a transition layer between the titanium alloy substrate and the hard TiN layer, which can strengthen the bonding force and reduce the problem of mismatch in physical and chemical properties between the coating and the substrate; the top TiN layer can provide high wear resistance.

[0027] 3) The process method provided by the present invention, without changing the power supply, target material, and electromagnetic field, on the basis of existing equipment conditions, prepares a composite titanium nitride coating with low surface roughness by exploring the hanging height of the matrix material sample and the rotation angle compared to the cathode arc target material, and then uses the physical blocking of the micron-level porous metal filter to finally obtain a composite titanium nitride coating less than 100nm, which meets the requirements of the state for the quality of the friction interface in the field of artificial joints. Therefore, the coating-titanium alloy material prepared by the process method of the present invention can be used for the preparation of artificial joints, which has great economic value. At the same time, since the process method of the present invention does not change the inherent conditions of the equipment and does not introduce other expensive mechanical equipment, it also has the conditions for industrial expansion of production, its cost is controllable, and the results are reliable. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.

[0029] Figure 1 This is a schematic diagram of the core process flow and process indicators of the present invention;

[0030] Figure 2 A schematic diagram of the coating-substrate material structure prepared in one of the embodiments;

[0031] Figure 3Schematic diagram of the structure of the vacuum coating equipment (a is a schematic diagram of the overall structure, b is a schematic diagram of the fixed position of the sample rack);

[0032] Figure 4 It is a schematic diagram of the hanging position of the matrix material on the sample rack;

[0033] Figure 5 A schematic diagram of the substrate material and mask setting on the sample holder;

[0034] Figure 6 The SEM morphology images of the coating sample surfaces at different positions (corresponding to samples S1-S4, respectively);

[0035] Figure 7 The optical super depth of field images of the coating sample surface at different positions (corresponding to samples S1-S4 respectively);

[0036] Figure 8 White light interference three-dimensional morphology images of the coating sample surface at different positions (corresponding to samples S1-S4 respectively);

[0037] Fig. 9 This is the friction coefficient curve when the S1-S4 coating samples are rubbed against the PTFE ball. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0039] Herein "and / or" includes any and all combinations of one or more of the associated listed items.

[0040] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.

[0041] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0042] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.

[0043] In this specification, some embodiments may be disclosed in a format of being within a certain range. It should be understood that such description of "being within a certain range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values ​​within this range. For example, the range The description of should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6 etc., as well as individual numbers within this range, for example, 1, 2, 3, 4, 5, and 6. The above rules apply regardless of the breadth of the range.

[0044] Example 1

[0045] This embodiment provides an example of a method for preparing a titanium nitride coating material.

[0046] 1. Preparation of substrate materials

[0047] The 3D printed titanium alloy is used as the base material (referred to as the base material), and the base material is polished and pre-treated before coating. The size of the base material in this embodiment is 17mm×17mm×3mm. Before depositing the coating, the 3D printed polished titanium alloy base is first placed in anhydrous ethanol and acetone for ultrasonic cleaning for 15 minutes to remove oil and other impurities on the surface; then the residual liquid on the surface is dried with a hair dryer for standby use.

[0048] 2. Preparation of coating materials

[0049] 1) Sample clamping. The 3D printed titanium alloy substrate material after the above pretreatment is placed in a vacuum coating device (hereinafter referred to as the device, the schematic diagram of the vacuum coating device used in the present invention is shown in Figure 2 ) on a sample holder, and fix it with a special clamp so that it is firmly fixed on the sample holder and can form a good circuit conduction with the sample holder. Use a bracket to set a mask with an aperture of 100-300μm in front of the base material, and the distance between the mask and the base material is 10-15mm, see Figure 5 Then, the sample holder was placed in the coating chamber of the equipment, and the chamber was evacuated by mechanical pump and molecular pump. -5 Torr, the sample was pretreated before coating.

[0050] 2) Sample etching pretreatment. After the vacuum degree of the coating chamber reaches the set value, open the chamber and heat it to 300°C. After the temperature reaches the set value, start the etching process. Rotate the sample holder to the front of the anode layer ion beam, introduce argon gas into the anode layer linear ion beam and ionize it. + Ions etch and clean the surface of the substrate material to remove the oxide film formed on the surface of the sample in the air, so as to increase the bonding strength between the subsequent coating material and the substrate material. The specific processing process is as follows:

[0051] Ion beam setting current: 0.7A

[0052] Ar gas flow rate: 60-120sccm,

[0053] Set voltage: 1200V

[0054] The cavity pressure was kept constant at 2.0 mTorr by adjusting the airflow, and the output power was 120 W.

[0055] Substrate negative bias: -800V

[0056] Etching time: 60min

[0057] Rotation speed: 15rpm

[0058] 3) Preparation of Ti / TiN composite coating deposition

[0059] The present invention selects a soft Ti layer as a transition layer between the titanium alloy substrate and the hard TiN layer, which plays a role in strengthening the bonding force and reducing the mismatch between the physical and chemical properties of the coating and the substrate; the top TiN layer is a functional layer that provides high wear resistance. The overall coating structure is a double-layer structure, with the Ti layer deposited first and then the TiN layer deposited. The coating structure is as follows Figure 2 As shown in the figure, the deposition thickness of the Ti layer in the Ti / TiN coating is 0.1-0.5μm; the deposition thickness of the TiN layer is 3.0-3.5μm, and the overall thickness of the coating is 3.5-4.0μm. The coating thickness varies slightly depending on the deposition time.

[0060] Depend on Figure 3 and Figure 4 As can be understood from the schematic diagram, the sample holder is placed above the revolving rotating frame, and the equipment can be adjusted to fix the sample holder in a specific position; in addition, the sample holder itself can be rotated to achieve uniform coating preparation during the coating process. The preparation process of Ti / TiN coating is as follows.

[0061] The first Ti layer: cathode arc target current 65A, argon flow rate 150sccm, chamber pressure controlled 45mTorr, substrate negative bias -60V, chamber temperature 300℃-350℃. Deposition time 10-20 minutes.

[0062] Second TiN layer: cathode arc target current 70A, nitrogen flow 250sccm, chamber pressure 45mTorr, substrate negative bias -120V, chamber temperature 200℃-350℃. Deposition time 2-4 hours.

[0063] Example 2

[0064] This example provides a key process verification of the low roughness titanium nitride coating prepared by the present invention

[0065] First, the hanging position of the base material is adjusted, and the hanging height of the base material is adjusted upward within the range of 0-90° based on the horizontal direction of the cathode arc target material, and the hanging height range of the base material is determined based on the surface roughness of the Ti / TiN coating being no greater than 600nm (Ra≤600nm). In this embodiment, the surface roughness data of the coating measured at two angles perpendicular to the horizontal direction of the cathode arc target material are listed in the following Table 1.

[0066] Table 1 Surface roughness data of samples with different suspension heights

[0067] Experimental Group Suspension Angle Horizontal Angle Roughness Ra(μm) A1 50° 0° 0.61 A2 60° 0° 0.53

[0068] Note: The horizontal angle of 0° is the fixed angle at which the sample holder faces the cathode arc target.

[0069] The surface roughness of the Ti / TiN coating is not greater than 600nm (Ra≤600nm). The sample suspension height is determined based on the horizontal direction of the cathode arc target, within the range of 60-90° upwards.

[0070] Secondly, turn off the sample holder revolution setting of the vacuum coating equipment, adjust the sample holder to a specific angle relative to the front of the cathode arc target, the specific angles include 0°, 45° and 60°, and the fixed angle of the sample holder is determined based on the surface roughness of the Ti / TiN coating being no greater than 350nm (Ra≤350nm).

[0071] The fixed angles set relative to the front of the cathode arc target include 0°, 45° and 60°, which are respectively denoted as angle (1), angle (2) and angle (3). Figure 3 b. No mask was used before each deposition of the substrate material, and finally samples S1, S2 and S3 were prepared, and the result data are as follows.

[0072] Table 2 Surface roughness data of samples with different sample holder fixing angles

[0073] Experimental Group Suspension Angle Horizontal Angle Roughness Ra(μm) S1 60° 0° 0.53 S2 60° 45° 0.31 S3 60° 60° 0.18

[0074] As can be seen from Table 2, when the fixed angle is 45°, the coating sample shows that the roughness has dropped from 0.53 μm to 0.31 μm, and when the fixed angle is 60°, it even drops below 0.20 μm.

[0075] Finally, a group of settings were made to fix the angle at 45°, angle (2), and a mask was used in front of the substrate material. Finally, sample S4 was prepared, and the results are as follows.

[0076] Table 3 Surface roughness data of samples without and with mask

[0077] Experimental Group Suspension Angle Horizontal Angle Mask Roughness Ra(μm) S2 60° 45° × 0.31 S4 60° 45° √ 0.09

[0078] The results show that when the upper mask is added in front of the S2 sample, the coating surface roughness is only 0.09 μm. It can be understood that when the mask is added in front of the S3 sample, the surface roughness of the coating will be even lower.

[0079] Four groups of Ti / TiN multilayer coating samples with different surface roughness were prepared and image verification was performed respectively.

[0080] Experimental results:

[0081] The surface SEM morphology images, surface optical super depth of field images and surface white light interference three-dimensional morphology images of the coating samples of the four groups of samples are shown in Figure 6 , Figure 7 and Figure 8 Among them, from Figure 6 It can be seen intuitively that among S1-S3, the surface of S1 (0°) has the most particles and is the roughest; the surface of S3 (60°) has fewer particles, but the particles are the largest; the surface of S2 (45°) has fewer particles than the surface of S1, and the particle size is smaller than that of the surface of S3. The surface of sample S4 with a mask has almost no rough particles.

[0082] In the S4 sample obtained in this embodiment, the thickness of the Ti layer is 0.5 μm, the thickness of the TiN layer is 3.35 μm, and the overall thickness of the Ti / TiN coating is 3.85 μm.

[0083] Fig. 9 The friction coefficient curves of samples with different roughness when grinding against PTFE balls show that the S4 sample with the lowest roughness has a lower and more stable friction coefficient, while the other samples have obvious fluctuations and higher friction coefficients, indicating that coating samples with a roughness lower than 20nm are more conducive to improving the tribological properties of the samples.

[0084] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing a low-roughness composite titanium nitride coating, characterized in that: The preparation method comprises the following steps: S01: using titanium alloy as a base material, and performing a polishing process on the base material; S02: placing the polished substrate on a sample rack of a vacuum coating device and fixing it, placing the sample rack in a coating chamber of the vacuum coating device for evacuation; further placing a mask in front of the substrate, wherein the aperture of the mask is in the range of 100-300 μm; S03: rotating the sample holder to the front of the anode layer ion beam, introducing argon gas to ionize the sample holder using the anode layer linear ion beam, and etching the surface of the substrate material using the ionized energetic ions to remove the oxide film; S04: depositing a first Ti layer on the surface of the substrate material, the deposition conditions are: cathode arc target current 65A, argon flow rate 150 sccm, controlled chamber pressure 45 mTorr, substrate negative bias voltage -60 V, chamber temperature 300°C-350°C, deposition time 10-20 minutes; then depositing a second TiN layer, the deposition conditions are: cathode arc target current 70A, nitrogen flow rate 250 sccm, controlled chamber pressure 45 mTorr, substrate negative bias voltage -120 V, chamber temperature 200°C-350°C, deposition time 2-4 hours; the specific operation is to first adjust the hanging position of the substrate material, take the horizontal direction of the cathode arc target as a reference, adjust the hanging height of the substrate material upward within the range of 0-90°, and determine the hanging height range of the substrate material based on the surface roughness of the Ti / TiN coating being no more than 600nm; then close the sample holder revolution setting of the vacuum coating equipment, adjust the sample holder to a specific angle relative to the front of the cathode arc target, keep the sample holder rotating, and make the substrate material rotate at a fixed angle relative to the front of the cathode arc target; the specific angle relative to the front of the cathode arc target includes 0°, 45° or 60°, and the fixed angle of the sample holder is determined based on the surface roughness of the Ti / TiN coating being no more than 350nm; finally, the low-roughness composite titanium nitride coating is prepared on the titanium alloy.

2. The preparation method according to claim 1, characterized in that The hanging height of the base material is within the range of 60-90° upwards based on the horizontal direction of the cathode arc target.

3. The preparation method according to claim 1, characterized in that: The sample holder is fixed at a position of 45° or 60° relative to the front of the cathode arc target; the sample holder rotates at 10-20 rpm.

4. The low-roughness composite titanium nitride coating-titanium alloy material prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The composite titanium nitride coating in the low-roughness composite titanium nitride coating-titanium alloy material is a Ti-TiN double-layer structure; The Ti layer is a transition layer between the titanium alloy substrate and the TiN layer; the thickness of the Ti layer is 0.1-0.5 μm; the thickness of the TiN layer is 3.0-3.5 μm, and the overall thickness of the coating is 3.5-4.0 μm; the surface roughness of the composite titanium nitride coating is less than 100 nm.

5. Use of the low-roughness composite titanium nitride coating-titanium alloy material according to claim 4 in the preparation of titanium alloy artificial joints.

Citation Information

Patent Citations

  • A process for preparing nitrogen-based hard coatings by adjustable magnetic field arc ion plating

    CN107338409B

  • Low-roughness titanium nitride coating for friction surface of artificial joint and preparation method of low-roughness titanium nitride coating

    CN117448827A